Examining the Impact of Tislelizumab Added to Chemotherapy on Health-Related Quality-of-Life Outcomes in Previously Untreated Patients With Nonsquamous Non–Small Cell Lung Cancer. Issue 2 (March 2022) - Lu, Shun; Yu, Yan; Barnes, Gisoo; Qiu, Xiusong; Bao, Yuanyuan; Tang, Boxiong
Abstract : Purpose: This study assessed the effects of tislelizumab, a programmed cell death protein 1 inhibitor, in combination with chemotherapy versus chemotherapy alone as first-line treatment on health-related quality of life (HRQoL) in patients with advanced nonsquamous non–small cell lung cancer (nSQ-NSCLC). Methods: Patients in this randomized, open-label, multicenter phase III study RATIONALE 304 (NCT03663205) with histologically confirmed stage IIIB/IV nSQ-NSCLC were randomized 2:1 to tislelizumab plus platinum-pemetrexed (arm T + PP) or platinum-pemetrexed alone (arm PP). Health-related QoL was measured using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 items and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire–Lung Cancer. Key patient-reported outcome endpoints include mean score change from baseline at weeks 12 (during chemotherapy) and 18 (following chemotherapy) in the 30-item Quality of Life Questionnaire Core's global health status/quality of life (GHS/QoL) and time to deterioration in GHS/QoL. Results: Three hundred thirty-two patients received at least 1 dose of study drug and completed at least 1 HRQoL assessment. Global health status/QoL score improved in arm T + PP at week 18 (between-group least square mean difference, 5.7; 95% confidence interval [CI], 1.0–10.5; P = 0.018). Patients in arm T + PP experienced greater reduction in coughing (−5.9; 95% CI, −11.6 to −0.1; P = 0.044), dyspnea (−3.8; 95% CI, −7.8 to 0.1; P = 0.059), chest pain (−6.2; 95% CI, −10.8 to −1.6; P = 0.008), and peripheral neuropathy (−2.6; 95% CI, −5.5 to 0.2; P = 0.066). Median time to deterioration in GHS/QoL was not achieved for either arm. Discussion: The addition of tislelizumab to platinum-based chemotherapy was associated with improvements in nSQ-NSCLC patients' HRQoL as well as the important disease-specific symptoms of coughing, chest pain, and dyspnea. ClinicalTrials.gov Identifier: NCT03663205